2006
DOI: 10.1164/rccm.200505-693oc
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes, Health Care Use, and Costs of Survivors of Acute Respiratory Distress Syndrome

Abstract: Survivors of ARDS continued to have functional impairment and compromised health-related quality of life 2 yr after discharge from the ICU. Health care use and costs after the initial hospitalization were driven by hospital readmissions and inpatient rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
316
2
16

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(350 citation statements)
references
References 23 publications
16
316
2
16
Order By: Relevance
“…Based on available data, in the UK and Ireland it is estimated that up to 45000 cases of ALI occur, with an estimated 13000-22000 deaths per year in patients with ALI (Brun-Buisson, Minelli et al 2004;Rubenfeld, Caldwell et al 2005;. Only 54% of survivors are able to return to work 12 months after hospital discharge (Cheung, Tansey et al 2006). The high incidence, mortality, long-term consequences and high economic costs mean that ALI is an extremely important problem.…”
Section: Background Informationmentioning
confidence: 99%
“…Based on available data, in the UK and Ireland it is estimated that up to 45000 cases of ALI occur, with an estimated 13000-22000 deaths per year in patients with ALI (Brun-Buisson, Minelli et al 2004;Rubenfeld, Caldwell et al 2005;. Only 54% of survivors are able to return to work 12 months after hospital discharge (Cheung, Tansey et al 2006). The high incidence, mortality, long-term consequences and high economic costs mean that ALI is an extremely important problem.…”
Section: Background Informationmentioning
confidence: 99%
“…MCI is a clinical condition defined by the presence of the following criteria 65À67 :(1) the person is neither normal nor demented (does not meet DSM-IV criteria for a dementia syndrome); (2) there is evidence of cognitive deterioration shown by either objectively measured decline over time and/or subjective report of decline by self and/or informant in conjunction with objective cognitive deficits; (3) the activities of daily living (i.e., taking medication, use of telephone, managing money, transportation, shopping and housework) are preserved, and complex instrumental functions are either intact or minimally impaired. MCI is further classified into four different subtypes according to specific neurocognitive deficits assessed through neuropsychological testing, though controversy exists about the stability of these more narrow constructs: (1) MCI amnestic: when only memory impairment is detected; (2) MCI multidomain amnestic: no memory impairment and multiple impairments in other neuropsychological domains (e.g., language and visuospatial); (3) MCI multidomain non-amnestic: more than one neuropsychological domain is impaired and the memory is normal; and (4) MCI single non-memory: one single neuropsychological domain is impaired and there is no memory impairment.…”
Section: And Dementiamentioning
confidence: 99%
“…1 The advancements in the medical treatments in the last years have led to a handful number of patients surviving a critical illness. 2 It has been progressively reported that these patients experience an acute and long-term morbidity in the form of cognitive, functional and emotional impairments along with diminished health-related quality of life. 2,3 Delirium is the most common form of acute brain dysfunction, which affects up to 80% of critically ill patients during an ICU stay, according to the severity of illness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations